Cardiovascular Preventive Activities and its Associated Factors Among Female Nurses in Universiti Sains Malaysia Hospital - Mohamed, Nik Siti Fatimah; Yusoff, Siti Suhaila Mohd; Zin, Faridah Mohd (Jurnal Keperawatan Priority, 2025)
Cardiovascular diseases (CVDs) are the leading cause of death globally, significantly impacting healthcare providers, including nurses. Despite their critical role in health promotion, many nurses neglect their cardiovascular preventive activities (CVPAs). This study assessed the prevalence and associated factors of good CVPAs among female nurses at Universiti Sains Malaysia (USM) Hospital. 212 registered female nurses participated in a cross-sectional study that was carried out between June and August 2015. Data on sociodemographic characteristics, work-related factors, and CVPAs were collected through a structured self-administered questionnaire. Good CVPAs were defined as adherence to dietary guidelines, regular physical activity, non-smoking, alcohol avoidance, and regular health screenings. Logistic regression analysis was used to identify factors associated with good CVPAs. Only 14.2% of nurses practiced good CVPAs. While 75.5% were physically active, only 17.9% consumed five or more servings of fruits and vegetables regularly. Nurses in medical-based departments had lower odds of practicing good CVPAs compared to those in surgical-based units (OR = 0.24, 95% CI: 0.08-0.76, p = 0.015). The prevalence of good CVPAs among female nurses at USM Hospital is low, especially regarding dietary adherence. The work department significantly influences preventive practices, suggesting the need for targeted interventions to promote cardiovascular health among nurses.